LENGTH-WEIGHT RELATIONSHIP OF SNOW TROUT SCHIZOTHORAX RICHARDSONII (GRAY) FROM THE UTTARKASH DISTRICT OF UTTARAKHAND STATE, INDIA. - NEGI, R. K.; NEGI, TARANA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Growth studies of Schizothorax richardsonii (Gray), using length-weight relationship were conducted on 70 specimens collected from the Yamuna and Kamal rivers of Uttarakashi district of Uttrakhand state, India. The statistical relationship between length-weight of the fish was derived as suggested by parabolic equation ( Le Cren, 1951). The 'n' value of length-weight relationship has been found to be 2.859. The values obtained for the mean length of pooled data were significant (p<0.01). A significant high correlation (r-0.9840) was found between the length and weight of the sample under study.